2016
DOI: 10.1016/j.foodcont.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders' perceptions, attitudes and practices towards risk prevention in the food chain

Abstract: An online survey was conducted to describe stakeholders' perceptions, attitudes and practices towards risk prevention in the food chain and to explore if common features could be extracted from different fields of competency or groups of stakeholders. Out of 80 participants, 60% believed that pathogenic microorganisms were the main hazard to prevent. Twenty-four percent perceived climate change as the main risk factor. Seventy-three percent believed that hazards in the food chain are preventable and they often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…More research is needed on incentives of abattoirs to implement preventive measures, taking into account differences between animal species and company size. In this study, the most frequently mentioned incentive was scientific proof (54%), which is similar to the finding of Lupo et al (). Furthermore, Lupo et al () found that the cost–benefit balance is an incentive.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…More research is needed on incentives of abattoirs to implement preventive measures, taking into account differences between animal species and company size. In this study, the most frequently mentioned incentive was scientific proof (54%), which is similar to the finding of Lupo et al (). Furthermore, Lupo et al () found that the cost–benefit balance is an incentive.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the most frequently mentioned incentive was scientific proof (54%), which is similar to the finding of Lupo et al (). Furthermore, Lupo et al () found that the cost–benefit balance is an incentive. In this study, only 16% of the respondents mentioned the importance of economic incentives.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most of them were known professional contact points who were previously or at the time involved in animal or human health activities. A snowball sampling strategy was then used (Lupo et al, 2016) where certain first wave respondents were asked to distribute the questionnaire link to other pertinent persons via e-mail. Therefore, the same email was sent by the OIE to country focal points responsible for notifying animal diseases.…”
Section: Study Design and Samplingmentioning
confidence: 99%